2004
DOI: 10.1159/000080587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Fluoridation Measures on Erosion Progression in Human Enamel and Dentine in situ

Abstract: The aim of the present study was to evaluate the effects of fluoride on erosive mineral loss in human enamel and dentine using a cyclic de- and remineralisation model in situ. The study was a three-treatment (5 days each) crossover design involving 4 (enamel) or 6 (dentine) healthy volunteers. Samples were recessed in palatal mouth appliances and worn day and night except during meals and were demineralised extraorally with 0.05 M citric acid (pH 2.3) for 6 × 5 min daily. Fluoridation was performed with toothp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
143
1
68

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(223 citation statements)
references
References 62 publications
11
143
1
68
Order By: Relevance
“…LMR is less sensitive to minute changes in mineral content than TMR, because of the use of thicker specimens as compared with TMR. Using LMR, erosion progression in both enamel and dentin has also been assessed [91][92][93] [69][70][71]. In these studies, the method has shown to be suitable to allow for distinction of different preventive treatment modalities resulting in different mineral loss.…”
Section: Chemical Analysis Of Minerals Dissolved In the Erosive Agentmentioning
confidence: 99%
“…LMR is less sensitive to minute changes in mineral content than TMR, because of the use of thicker specimens as compared with TMR. Using LMR, erosion progression in both enamel and dentin has also been assessed [91][92][93] [69][70][71]. In these studies, the method has shown to be suitable to allow for distinction of different preventive treatment modalities resulting in different mineral loss.…”
Section: Chemical Analysis Of Minerals Dissolved In the Erosive Agentmentioning
confidence: 99%
“…17 As high concentrated fluoride agents or a prolonged application time might lead to a thicker and more stable CaF 2 -precipitate, an intensive fluoridation is considered as most effective for prevention of erosive enamel loss. 4,13 While most studies focused on the impact of the fluoride concentration and the pH-value of the fluoride agent on erosion, only few studies compared the efficacy of fluorides with respect to the fluoride compound. Thereby, SnF 2 containing toothpastes and solutions showed a better protective capability against erosion-like lesions than NaF agents.…”
Section: Introductionmentioning
confidence: 99%
“…1,8,10,11,16,23,24 The in situ study design here using two erosive challenges per day (0.65% citric acid, pH 3.6) appears relatively slight but should reflect situations that can occur in patients with incipient erosion (2.7 μm -4.8 μm). [25][26][27] As expected, in the present study, the profilometric analysis showed that the lowest tissue loss was observed in the fluoride-treated group (AmF/NaF/SnCl 2 solution containing 500 ppm F -, 800 ppm Sn 2+ , pH = 4.5) compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…1 Successful results on the reduction of dental demineralization by erosive acids have been shown with polyvalent metal ion-containing products, such as stannous, in several in vitro studies 3,4,5,6,7 and confirmed by other in situ studies. 8,9,10,11 Authors have reported the use of tin-ion in different presentation, such as solutions, toothpastes, gels and varnishes.…”
Section: Introductionmentioning
confidence: 99%